2008
DOI: 10.1158/1535-7163.mct-07-0382
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-expressed human hyperplasia suppressor gene induces apoptosis in cancer cells

Abstract: Hyperplasia suppressor gene (HSG), also called human mitofusin 2, is a novel gene that markedly suppresses the cell proliferation of hyperproliferative vascular smooth muscle cells from spontaneously hypertensive rat arteries. This gene encodes a mitochondrial membrane protein that participates in mitochondrial fusion and contributes to the maintenance and operation of the mitochondrial network. In this report, we showed that an adenovirus vector encoding human HSG (Ad5-hHSG) had an antitumor activity in a wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 22 publications
2
36
0
Order By: Relevance
“…Using Western blot analysis and RT-PCR analysis, we found that Mfn2 protein and mRNA levels were significantly lower in CRC tissues than in corresponding normal tissues. Overexpression of Mfn2 protein mediated by adenovirus has a significant anti-proliferative effect in a wide range of cancer cell lines [8]. Our results indicate that Ad-Mfn2 also had a significant anti-proliferative effect in HCT116, HT-29, and SW480 cells.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Using Western blot analysis and RT-PCR analysis, we found that Mfn2 protein and mRNA levels were significantly lower in CRC tissues than in corresponding normal tissues. Overexpression of Mfn2 protein mediated by adenovirus has a significant anti-proliferative effect in a wide range of cancer cell lines [8]. Our results indicate that Ad-Mfn2 also had a significant anti-proliferative effect in HCT116, HT-29, and SW480 cells.…”
Section: Discussionmentioning
confidence: 53%
“…The anti-proliferative effect of Mfn2 is comparable to that of the well-known tumor suppressor p53 [5,8]. We demonstrated previously that Mfn2 is a novel p53-inducible target gene in hepatocellular carcinoma cells [9].…”
mentioning
confidence: 74%
“…Optical density (OD) was read at 570 nm using a spectrophotometer microplate reader (Labsystems, Finland). The inhibition of islet cells caused by different concentrations of VPA was calculated using the formula: inhibition rate (%) = 100 x (1 -[OD drug exposure / OD control ]) (Wu et al, 2008).…”
Section: Mtt Assaymentioning
confidence: 99%
“…Several lines of evidence indicate that mfn-2 modulates mitochondrial metabolism by regulating mitochondrial membrane potential, fuel oxidation, and the oxidative phosphorylation system [11,12] . Recent evidence also shows that mfn-2 inhibits tumor cell proliferation and increases their sensitivity to chemotherapy and radiotherapy even above p53 [13] . In addition, recent study has shown that mfn-2 exhibits a profound anti-proliferative effect on VSMCs in vitro and in vivo via inhibition of the Ras-Raf-MEK-ERK1/2 MAPK signaling pathway [14] , and promotes VSMC and cardiomyocyte apoptosis via the mitochondrial death pathway [15,16] .…”
Section: Introductionmentioning
confidence: 98%